2021
DOI: 10.1017/jmo.2022.1
|View full text |Cite
|
Sign up to set email alerts
|

Managers and telework in public sector organizations during a crisis

Abstract: Through the use of a narrative-interview approach and contingency theory as research methods, this study explores the teleworking behaviors of N = 41 public managers when remotely managing and leading their organizations as virtual bureaucracies during the Covid-19 lockdown. Its findings suggest that their role set was underscored by communal and supervisory tasks. Managers were confronted with environmental challenges of emotional nature (e.g., anxieties). But they also associated teleworking with improving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…While our participants noted that these opportunities increased transparency and knowledge transfer, they might not benefit all roles equally. In fact, in other virtual work literature, managers had more meetings than non-managers (Cecchi et al 2022 ) and found redundant communication overwhelming and blurred the lines between work and home (Dandalt 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…While our participants noted that these opportunities increased transparency and knowledge transfer, they might not benefit all roles equally. In fact, in other virtual work literature, managers had more meetings than non-managers (Cecchi et al 2022 ) and found redundant communication overwhelming and blurred the lines between work and home (Dandalt 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…, 2019). Indeed, remote working has created a virtual work environment whereby normal hierarchical and interpersonal relationships are disrupted, and in which there is a greater need for organizations to provide organizational members with communal resources in addition to more typical work resources (Dandalt, 2021). It would thus be important for future research to consider how occupying a managerial position might influence the likely impact of CN on professional and personal experiences in different work settings (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they may be more likely to succumb to the pressure of being constantly available to respond to work-related messages and demands relative to non-managerial employees. In addition, managers working remotely tend to adjust their behaviors, priorities, and managerial styles to meet the needs of their organization to a far greater extent than regular employees (Dandalt, 2021). Moreover, they also typically fail to receive the same amount of psychological support from their organization than regular employees working remotely, despite experiencing more work-related anxieties.…”
Section: Limitations and Research Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currie and Eveline (2011) reported the flexible practices of remote work can lead to work extensification and intensification. With workers able to work anywhere at anytime, many end up working longer hours, or face role overload by taking on too many duties (Currie and Eveline, 2011;Dandalt, 2021;Kumpikait_ e-Vali unien_ e et al, 2021;Palumbo, 2020). Overall, there are mixed findings regarding the role of remote work in improving WLB, making it likely that there are complex situational interactions to be considered (i.e.…”
Section: The Moderating Role Of Remote Workmentioning
confidence: 99%